Evaluasi Metode Instalasi Sensor Kapasitif Berbiaya Rendah untuk Pemantauan Kadar Air Tanah pada Lereng Berbasis IoT: Evaluation Of Low-Cost Capacitive Sensor Installation Methods For IoT-Based Soil Moisture Monitoring On Slopes - Muhammad Azhar (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study evaluates the effect of installation methods of low-cost capacitive soil moisture sensors on field measurement performance. Six sensors were tested using two installation methods, namely side mount and bottom mount, at three depth variations (0.2 m, 0.5 m, and 1 m). A monitoring system was developed using an ESP32 microcontroller integrated with the Firebase cloud platform for real-time data acquisition, powered by a solar panel. Field testing was conducted from March 10 to April 16, 2026, with GPM satellite rainfall data used as a supporting parameter. Calibration results showed a strong linear relationship between sensor output voltage and volumetric water content with R2>0.9 for all sensors. The bottom mount method produced valid readings from the beginning of the testing period with good response to rainfall events at all depths. In contrast, the side mount method experienced a delay in sensor–soil contact formation, resulting in invalid data during the early phase. The findings indicate that the quality of physical contact between the sensor and soil is a key factor in reading reliability, and the bottom mount method is more effective for long-term field soil moisture monitoring.